Magnólia (1999), de Paul Thomas Anderson em três canções: a música pop e o videoclipe como elementos estruturais - Cleiton Rafael Ferreira Lopes (2023)
The main objective of this research is to understand deeply the relationship between cinema and music video, having as the object of study the film Magnolia (1999), by the North American director Paul Thomas Anderson. To achieve this goal, we first sought to understand the origins of the music video and identify the main characteristics of the format. From there, we analyzed the director’s filmography, who also directed music videos, to understand how to relate his film work with pop music. After that, we can analyze Magnolia, taking the songs of singer Aimee Mann as the based its script. We highlighted three scenes from the feature film where music plays an important role: the opening scene with the song "One," the film climax with "Wise Up," and the final scene with "Save Me." As a result, the research found a construction that is very close, when not properly said, to a music video in the three highlighted scenes and in the film as a whole.